Benchmarking density functionals in conjunction with Grimme's dispersion correction for noble gas dimers (Ne2, Ar2, Kr2, Xe2, Rn2). Issue 9 (9th February 2017) - Kovács, Attila; Cz. Dobrowolski, Jan; Ostrowski, Sławomir; Rode, Joanna E.
Abstract: Eleven exchange‐correlational functionals of different types corrected for dispersion by Grimme's D3 correction in conjunction with the aug‐cc‐pVTZ basis set were tested on the following noble gas (Ng) dimers: Ne2, Ar2, Kr2, Xe2, and Rn2 . For comparison, the D2 and D3BJ corrections were probed with the B3LYP functional. From post‐HF wavefunction methods, CCSD(T) theory was also included. The investigated properties involved potential energy curves, equilibrium bond distances, and interaction energies. The B3LYP‐D3, B3LYP‐D3BJ, and PBE0‐D3 functionals performed overall best for bond distances, while B3LYP‐D3 and B97‐D3 performed best for interaction energies. The importance of fortunate error cancellations was seen in the often reduced agreement with reference data upon correction for BSSE. As several functionals performed well selectively for some noble gases (and poorly for others), we also analysed the performance on the Ng2 dimers individually and recommended DFT‐D3 functionals for the calculation of large clusters of each Ng. Abstract : Grimme's recent D3 dispersion correction has been applied successfully in quantum chemical modeling of weak interactions, however, its performance for noble gases has not been tested in detail yet. The present study reports the benchmarking of eleven popular exchange‐correlational functionals extended with the D3 correction for noble gas interactions.